MERCURY ANALYSIS AND CONCENTRATION IN SEAWATER OF SOUTHERN SUMBAWA - Surya Hadi (Jurnal Pijar Mipa, 2009)
Abstract. Current concerns over the negative impacts of Hg in the environment have led to the rapid progress of studies in this area. This progress has been directed to obtain analysis techniques that are able to accurately quantify Mercury (Hg) at extremely low concentration in which it frequently occurs. As part of a study on the environmental aspects of deep-sea submarine tailing placement at the Batu Hijau Mine, Sumbawa, this paper discusses recent progress in Hg analytical techniques, followed by the application of several techniques to investigate Hg concentration in seawater in the vicinity of the tailing discharge location. Using cold vapour atomic fluorescence spectrometry, dissolved Hg was found to be at sub-ng/l (ppt) levels. No dissolved Hg signal associated with the tailing discharge was found with concentrations being similar to adjacent coastal waters.ÃÂ Key words: tailing, STP system, Hg, analysis, and marine water